2015
DOI: 10.17795/bhs-30402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fenugreek (Trigonella foenum-graecum) Seed and 17-β Estradiol on Serum Apelin, Glucose, Lipids, and Insulin in Ovariectomized Rats

Abstract: Background: Menopause, a natural phenomenon, is defined by the fall of ovarian hormones mainly estrogens causing major problems such as insulin resistance. Fenugreek (Trigonella foenum-graecum) is known to have some useful properties such as insulin sensitizing effect. Apelin is an adipokine, which has several roles such as regulation of insulin secretion. Objectives: The objective of the present study was to evaluate the effect of fenugreek seed and 17-β estradiol on serum Apelin along with glucose, lipids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…These outcomes are constant with a previous study conducted by Abedinzade et al. (2015), which stated that OVX rats treated with ethanolic and hexonic extract (50 and 150 mg kg –1 day –1 ) of TFG seed extract declined the TC and TG levels (Abedinzade et al., 2015a). A recent study supports the estrogenic activity of the TFG seeds' aqueous extract that may be attributed to the phytoestrogens in OVX rats (Brogi et al., 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These outcomes are constant with a previous study conducted by Abedinzade et al. (2015), which stated that OVX rats treated with ethanolic and hexonic extract (50 and 150 mg kg –1 day –1 ) of TFG seed extract declined the TC and TG levels (Abedinzade et al., 2015a). A recent study supports the estrogenic activity of the TFG seeds' aqueous extract that may be attributed to the phytoestrogens in OVX rats (Brogi et al., 2019).…”
Section: Discussionsupporting
confidence: 84%
“…PE-TFG seed extract reduced the blood glucose levels. These results are supported by the earlier study where OVX rats treated with ethanolic (50 mg kg -1 day -1 ) and hexonic TFG (150 mg kg -1 day -1 ) for 6 weeks considerably decreased the glucose and insulin levels (Abedinzade et al, 2015a). Presence of glucomannan soluble fiber in PE-TFG seeds, which delays intestinal absorption of ingested sugars.…”
Section: Discussionsupporting
confidence: 83%
“…The HDL levels improved significantly in the rats fed with 400 mg/kg/day of the FG seed extract. The hypolipidaemic effect of FG can be attributed to: (i) the presence of dietary fibres and gum (fibres restrict the absorption of lipids by the small intestine), 12 (ii) the steroidal saponins present in the FG extract, which slow down the absorption of cholesterol, as well as the production of cholesterol by the liver, by decreasing the activity of the regulatory enzyme of the cholesterol synthesis pathway, i.e., β-hydroxy β-methylglutaryl CoA, 13 (iii) the 4-hydroxy isoleucine in FG, which acts on liver cells and adipocytes, leading to decreased cholesterol and TG synthesis, in addition to enhanced LDL receptor-mediated LDL uptake, and (iv) the increase in the activity of lecithin cholesterol acyl-transferase, thereby favouring the incorporation of a greater amount of cholesterol in HDL and increased cholesterol uptake by the liver 14 . Our results concur with those of the study by Praveen Kumar et al., which has suggested that supplementation of 0.5 and 1 g/kg/day of FG seed aqueous extract for four weeks significantly decreased the TC, TG, and LDL levels, and increased the HDL levels 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Kumar et al stated the hypolipidemic effect of Fenugreek seed extract on high--fat diet-induced obese rats [54]. Abedinzade et al in 2015 reported the antihyperlipidemic effect of fenugreek seed extract in ovariectomized rats [55]. The steroidal components (saponins and sapogenin) present in fenugreek seeds are responsible for hypolipidemic effect [56].…”
Section: Coumestansmentioning
confidence: 99%